Modulation of TNFα-driven neuroinflammation by Gardenin A: insights from in vitro, in vivo, and in silico studies - Chadha, Prashsti; Aghara, Hiral; Solanki, Harshrajsinh; Patel, Manali; Sharma, Dhrubjyoti; Thiruvenkatam, Vijay; Mandal, Palash (Frontiers in Pharmacology, 2025)
IntroductionChronic alcohol consumption is a major contributor to neuroinflammation, oxidative stress, and blood-brain barrier (BBB) disruption, leading to significant neuronal injury. Traditional therapies for alcohol use disorder (AUD) predominantly target behavioral and receptor-based mechanisms, often neglecting the direct pathophysiological impacts of alcohol on brain tissue. This study explores the neuroprotective potential of Gardenin A (GarA), a hexa-methoxylated flavone, in counteracting alcohol-induced inflammation and physiological damage.MethodsIn vitro experiments utilized SH-SY5Y neuroblastoma cells treated with varying concentrations of GarA, assessing cell viability, nuclear integrity, oxidative stress, and gene expression. In vivo experiments involved the administration of ethanol alongside GarA at doses of 50 and 100 mg/kg body weight to male Wistar rats. Subsequent brain tissue analysis employed histological and immunohistochemical methods to evaluate structural preservation and cellular responses. Key molecular targets were examined, including vimentin, brain-derived neurotrophic factor (BDNF), and Claudin5. Protein levels of inflammatory markers and antioxidant enzymes were quantified using ELISA, providing detailed insights into the biochemical pathways involved. Complementary in silico methods, such as molecular docking and network pharmacology, were employed to elucidate the mechanistic interactions and predict potential molecular binding sites.ResultsThe treatment with GarA resulted in enhanced neuronal viability and a reduction in ethanol-induced oxidative stress in vitro. In vivo results demonstrated preservation of brain architecture, attenuation of astroglial reactivity, and significant downregulation of tumor necrosis factor-alpha (TNFα), a key mediator of neuroinflammation. Additionally, GarA was associated with restored BDNF expression and upregulated antioxidant markers like HO-1 and Nrf2, maintaining neurovascular integrity and neurotrophic balance.DiscussionGarA demonstrates neuroprotective potential, with evidence suggesting modulation of neuroinflammation and oxidative stress that may involve TNFα and BDNF pathways. These promising findings suggest potential therapeutic applications for GarA in addressing alcohol-related neurodegeneration. Future research focusing on clinical trials may prove helpful in validating these preclinical findings. Expanding studies to include diverse animal models and exploring combinatory treatments with existing AUD therapies could enhance understanding and application. Such efforts may pave the way for incorporating GarA into comprehensive pharmacotherapeutic strategies aimed at mitigating the neuropathological effects of chronic alcohol consumption.